The Effects of ınteractive science notebook on student teachers’ achievement, study habits, test anxiety, and attitudes towards physics - Fajardo, Maria Teresa M. (Journal of Turkish Science Education, 2024)
This study aimed to examine the impacts of using Interactive Science Notebook on students’ achievement, study habits, test anxiety levels, and attitudes towards physics. An interactive notebooking strategy was introduced to student teachers, who were enrolled to a local university. The participants comprised of 37 sophomore student teachers taking General Physics 2 (Electricity & Magnetism). To collect data, their profiles were gathered using survey questionnaires that measure students’ learning style, study habit, test anxiety, and attitude towards physics as well as a physics achievement test. Through a pre-experimental research design, descriptive statistics and appropriate statistical analyses were conducted. The results indicated that the use of Interactive Science Notebook significantly improved student teachers’ physics achievement levels. It was also found out that their study habits, test anxiety levels and attitudes towards physics significantly predicted their physics achievement levels.
Keywords: Achievement; attitude in science; interactive science notebook; preservice science teachers; learning style; physics